IDENTIFIKASI JENIS-JENIS IKAN DI SUNGAI TEMBESI KECAMATAN MUARO SIAU KABUPATEN MERANGIN - Edi Sudrajat; Pitri Handayani; Andriyanto (BIOCOLONY, 2021)
This research was motivated by the absence of data on the identification of fish species in the Tembesi river. The study aims to determine the types of fish found in Tembesi River, Muaro Siau District, Merangin Regency. Research is a descriptive qualitative research using sampling techniques in the form of purposive sampling techniques. The results of this study amounted to 124 individuals, consisting of 11 species representing 4 families including Baung (Mestus nemorus), Dalum (Bagarius yarelli), Lais (Criptopterus limpok), langli (Botia macrachanta), Lampam (B.schwanenfeldi), semuruk ( Osteochilus melanopleura), malih (L Fasciatus), Semah (Tor Soro), Seluang (Rsaboraargyrotaenia), kebarau (Hampala macrolepidato), striped muju (Ostechilus haselti).